Issue Information. Issue 1 (3rd March 2020) - Unknown
Abstract : Cover : In Guilbert et al. (https://doi.org/10.1002/cptx.91 ), the image shows B lymphocyte development within the bone marrow. B cell differentiation proceeds along an ordered process. Stages can be defined by surface marker expression indicated by the lettered fraction (A–F).